A Happening at Danebury Hillfort – But When?. Issue 4 (November 2015) - Cunliffe, Barry; Farrell, Philip; Dee, Michael
Summary A group of six radiocarbon dates for human skeletons found at the Iron Age hillfort of Danebury are suggestive of a major killing event. We consider here how the dates, mitigated by a careful consideration of the archaeological evidence for context, can be used in constructing site history.